The Effect of Picture And Picture Type Cooperative Learning Model on Participation and Learning Outcomes of Grade IV Elementary School Students - Gustiawan, Ricky; Yeni Erita; Deni Okta Nadia; Nofia Henita (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2023)
This research is motivated by the participation and learning outcomes of fourth-grade students at SDN 15 Kapalokoto Kec. Sungaipua is still low. This can be seen that many students are less enthusiastic about learning. The research aims to determine the influence of the Picture and Picture Cooperative Learning Model on the Participation and Learning Outcomes of Class IV Elementary School Students. This research was conducted on fourth-grade students of SDN 15 Kapalokoto Kec. Sungaipua for the 2021/2022 academic year. The experimental research design used was a randomized control group-only design. Participation test data were obtained through student participation questionnaires. The results showed that: (1) There was an effect of student participation being taught a cooperative model of picture and picture type, (2) there was an effect of student learning outcomes taught a cooperative model of picture and picture type.